Comparison of the effects of tert-butyl hydroperoxide and peroxynitrite on the oxidative damage to isolated beef heart mitochondria - Kohutiar, Matej; Ivica, Joško; Vytášek, Richard; Skoumalová, Alice; Illner, Jan; Šantorová, Pavlína; Wilhelm, Jiří (Physiological research, 2016)
Isolated beef heart mitochondria have been exposed to tert-butyl hydroperoxide (tBHP) and peroxynitrite (PeN) in order to model the effects of reactive oxygen and nitrogen species on mitochondria in vivo. The formation of malondialdehyde (MDA), protein carbonyls, lipofuscin-like pigments (LFP), and nitrotyrosine was studied during incubations with various concentrations of oxidants for up to 24 h. The oxidants differed in their ability to oxidize particular substrates. Fatty acids were more sensitive to the low concentrations of tBHP, whereas higher concentrations of PeN consumed MDA. Oxidation of proteins producing carbonyls had different kinetics and also a probable mechanism with tBHP or PeN. Diverse proteins were affected by tBHP or PeN. In both cases, prolonged incubation led to the appearance of proteins with molecular weights lower than 29 kDa bearing carbonyl groups that might have been caused by protein fragmentation. PeN induced nitration of protein tyrosines that was more intensive in the soluble proteins than in the insoluble ones. LFP, the end products of lipid peroxidation, were formed more readily by PeN. On the other hand, fluorometric and chromatographic techniques have confirmed destruction of LFP by higher PeN concentrations. This is a unique feature that has not been described so far for any oxidant.
Keywords: zvířata; Animals; reaktivní formy dusíku; Reactive Nitrogen Species; tert-Butylhydroperoxide; Reactive Oxygen Species; Mitochondria, Heart; Cattle; srdeční mitochondrie; kyselina peroxydusitá; terc-butylhydroperoxid; skot; reaktivní formy kyslíku; Peroxynitrous Acid